SUPERIORITY OF ART OVER LIFE IN THE POETRY OF JOHN KEATS WITH REFERENCE ODE ON GRECIAN URN, ODE TO NIGHTINGALE, ODE ON MELANCHOLY AND ODE TO AUTUMN - Maimoona Kalsoom; Ms. Seema Gul (International Journal of Contemporary Issues in Social Sciences, 2024)
John Keats was the ultimate romantic, if not the ideal. He had the high idea that poetry exists for its own sake and must bear the cross whether it is committed to politics, philosophy, or any other subject, no matter how large or little .John Keats’ Odes are among his best-known poems. Keats died gradually, and he wrote about these small, fatal episodes. A blanket hug ending, an antique urn in the image, or harvesting crops in the fall are all examples and symbols of death. In his poems, Keats claimed that focusing on beauty may help to delay one’s impending death. The speaker in several of Keats’ poems escapes reality to enter a spiritual, mythological, or creative realm. By the end of the poem, the speaker has learned fresh understanding and is changed in some way as he returns to his normal life. Keats seemed to be reminding us in his poems that grief is a vital component of experience and must be accepted as a part of existence. The poet’s main topic throughout the poems appears to be his yearning to escape from the reality of human pain to an incomparably better realm of his own imagination. Even though he addresses melancholy in many of his poems, his references to the land, the natural world, love, and beauty make them feel more hopeful.